Reassessing Islamic Hedging Fatwa in Indonesia: Accounting, Regulation, and Market Practices - Rovila El Maghviroh; Indra Suwandi; Nurdina Nurdina (Universitas Islam Negeri Ar-Raniry, 2026)
Exchange rate volatility remains a major challenge for businesses, including institutions operating within the Islamic financial system. In Indonesia, Dewan Syariah Nasional–Majelis Ulama Indonesia Fatwa No. 96/DSN-MUI/IV/2015 serves as the primary reference for Sharia-compliant hedging transactions. However, concerns related to Sharia compliance, inconsistencies between regulations and market practices, and limited understanding of operational hedging mechanisms continue to hinder the development of the Islamic derivatives market. This study examines the reliability and practical applicability of the Fatwa through the perspective of PSAK Syariah, relevant regulations, and foreign exchange market practices. Using a qualitative approach, the study employs content analysis, comparative analysis, and critical analysis of the Fatwa and related accounting standards. The findings show that the Fatwa contains four hedging mechanisms: Aqd al-Tahawwuth al-Basith (ATB), al-Murakkab (ATM), and Aqd al-Tahawwuth fi Suq al-Sil’ah (ATFSS) Mechanism-1 and Mechanism-2. Among them, ATB, ATM, and ATFSS-1 are operationally capable of producing actual currency settlement, although ATFSS-1 introduces financing and operational complexities that reduce efficiency. Meanwhile, ATFSS-2 does not result in actual currency exchange because settlement occurs through netting. The study also identifies several misalignments between the Fatwa, accounting standards, financial regulations, and prevailing market practices, which may weaken the effectiveness and practical benefits of Sharia hedging transactions. This study contributes a new analytical framework for assessing the reliability and alignment of Sharia rulings with accounting governance, regulatory structures, and market realities in a dual banking environment. ABSTRAK - Menilai Ulang Fatwa Lindung Nilai Syariah di Indonesia: Akuntansi, Regulasi, dan Praktik Pasar. Volatilitas nilai tukar masih menjadi tantangan besar bagi dunia usaha, termasuk lembaga yang beroperasi dalam sistem keuangan syariah. Di Indonesia, Fatwa Dewan Syariah Nasional–Majelis Ulama Indonesia No. 96/DSN-MUI/IV/2015 menjadi rujukan utama transaksi lindung nilai berbasis syariah. Namun demikian, persoalan kepatuhan syariah, ketidakselarasan antara regulasi dan praktik pasar, serta keterbatasan pemahaman mengenai mekanisme lindung nilai masih menghambat perkembangan pasar derivatif syariah. Penelitian ini bertujuan menelaah keandalan dan daya terap Fatwa melalui perspektif PSAK Syariah, regulasi terkait, dan praktik pasar valuta asing. Penelitian menggunakan pendekatan kualitatif dengan metode analisis isi, analisis komparatif, dan analisis kritis terhadap Fatwa serta standar akuntansi terkait. Hasil penelitian menunjukkan bahwa Fatwa memuat empat mekanisme lindung nilai, yaitu Aqd al-Tahawwuth al-Basith (ATB), al-Murakkab (ATM), serta Aqd al-Tahawwuth fi Suq al-Sil’ah (ATFSS) Mekanisme-1 dan Mekanisme-2. ATB, ATM, dan ATFSS-1 terbukti mampu menghasilkan penyelesaian transaksi valuta asing secara nyata, meskipun ATFSS-1 menimbulkan kompleksitas pembiayaan dan operasional yang mengurangi efisiensi transaksi. Sebaliknya, ATFSS-2 tidak menghasilkan pertukaran valuta asing secara riil karena penyelesaian dilakukan melalui mekanisme netting. Penelitian ini juga menemukan adanya ketidakselarasan antara Fatwa, standar akuntansi, regulasi keuangan, dan praktik pasar yang dapat mengurangi efektivitas serta manfaat praktis transaksi lindung nilai syariah. Penelitian ini menawarkan kerangka analitis untuk menilai keselarasan fatwa syariah dengan tata kelola akuntansi, regulasi, dan praktik pasar dalam sistem perbankan ganda.